Strategic Self-Talk Assists Basketball Free Throw Performance Under Conditions of Physical Exertion - Evangelos Galanis; Antonis Hatzigeorgiadis; Fedra Charachousi; Alexander T. Latinjak; Nikos Comoutos; Yannis Theodorakis (Frontiers Media S.A., 2022)
The purpose of the present study was to examine the effects of a strategic self-talk intervention on basketball free throw performance under conditions of physical exertion. Forty-one male basketball players (Mage = 23.19 years) participated in the study. Following a baseline assessment, a 3-week intervention was implemented. During this period participants of the two groups practiced the same number of free throws in their training sessions; participants of the experimental group practiced using self-talk and developed personal free throw self-talk plans. In the final assessment, the participants repeated the free throw test following a typical shuttle run task causing increased physical exertion. The results showed that in the final assessment the self-talk group performed significantly better than the control group. Overall, the findings indicate that self-talk can be an effective strategy for basketball players when performing free throw under conditions of physical exertion, which is a typical situation in basketball games.